VALIDITY OF ANDROID BASED MOBILE LEARNING MEDIA IN COMPUTER AND BASED NETWORK VOCATIONAL HIGH SCHOOL - Mayefis, Reska; Sukardi, Sukardi; Usmeldi, Usmeldi (LPPM Undiksha, 2019)
The purpose of this research is to produce a valid android based mobile learning media that is suitable for learning in Computer and Based Network subjects. This android based mobile learning media is designed to increase student interest in learning, to improve student understanding about learning material and also to improve learning outcomes. This is a Research and Development (R&D) with 4-D model (Define, Design, Develop, Disseminate). In this study is limited to the development stage, is to know the validity of the mobile learning media from material and media experts. Data analysis techniques is descriptive analysis techniques to describe the validity of the android based mobile learning media. Media validity is measured through a validated instruments that has been previously validated. The validity results from this research are android based mobile learning media declared valid in terms of media aspects and material aspects. Based on the results of this validity, it is concluded that the android based mobile learning media was declared valid for use as Computer and Based Network learning media.